Systematic Literature Review: CAR, LDR, NIM and NPL on Banking Profitability in Indonesia: Ulasan Literatur Sistematis: CAR, LDR, NIM, dan NPL terhadap Profitabilitas Perbankan di Indonesia - Argha Cahyo Pradigdo; Nicko Albart; Nurul Huda (Universitas Muhammadiyah Sidoarjo, 2025)
This study aims to analyze the effect of financial ratios such as Capital Adequacy Ratio (CAR), Non-Performing Loan (NPL), Loan to Deposit Ratio (LDR), and Net Interest Margin (NIM) on Return on Assets (ROA) in the Indonesian banking sector. This study uses the Systematic Literature Review (SLR) method with the PRISMA approach to ensure transparency and replication of the study. The data used was taken from various journals published between 2019 and 2024 through the Google Scholar and Scopus databases. The conclusion of this study confirms that Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), and Net Interest Margin (NIM) generally have a positive impact on Return on Assets (ROA). Conversely, a Non-Performing Loan (NPL) has a negative impact on Return on Assets (ROA). However, in terms of significant influence, Capital Adequacy Ratio (CAR), Non-Performing Loan (NPL), Loan to Deposit Ratio (LDR), and Net Interest Margin (NIM) have varying significant influences on Return on Assets (ROA) depending on the internal and external conditions of the bank.